Religi Grebeg Sura di Banyumas - Subur Subur (IBDA` : Jurnal Kajian Islam dan Budaya, 2017)
This research reveals the religious values expressed by symbols of Grebeg Sura tradition in Tambaknegara, Rawalo District, Banyumas Regency. Islamic studies on Javanese context are endless because their dynamics and uniqueness are always interesting to be studied. As a religion, Islam gives concepts and symbols of idealism, while Javanese culture, having existed for hundreds of years, has born various and specific traditions and culture. Methods used in this research are observations and interviews to competent informants. This research reveals that Islam in the Javanese context cannot be separated from local culture and traditions that have been planted tightly. Islam can be accepted by Javanese society for its flexibility. The tradition of grebeg sura in Tambaknegara, Rawalo District, Banyumas Regency is full of Javanese symbols. However, it also contains values that are relevant to Islam. In perceiving polytheistic Javanese traditions, Muslims show three different attitudes: 1) extremely reject the traditions due to their principal that believing in magical power originated from animism and dynamism is categorized into syirik and will destroy their aqidah, therefore, it is not tolerable; 2) totally accept the tradition without any selection, which is usually followed by common people who do not really understand Islam, but they get benefits of it; 3) gradually and persuasively erase the traditions through preaching Islam using local symbols.Â Penelitian ini bertujuan mengungkap pesan-pesan religius yang disampaikan melalui simbol-simbol tradisi Grebeg Sura di Tambaknegara Rawalo Kab. Banyumas. Penelitian ini menggunakan metode observasi dan wawancara dengan narasumber yang kompeten. Hasil penelitian menunjukkan Islam dalam konteks Jawa tidak bisa dilepaskan dari berbagai budaya dan tradisi setempat yang mengakar begitu kuat. Islam dapat diterima oleh masyarakat karena keluwesannya. Kegiatan Grebeg Sura di Â Desa Tambaknegara memang sarat akan simbol-simbol yang begitu kental dengan warna Kejawen, tetapi banyak juga nilai yang relevan dengan substansi nilai Islam. Dalam memandang tradisi Jawa yang politheistik, terdapat tiga sikap muslim; Pertama, sikap yang menolak secara ekstrem, karena berpendapat bahwa mempercayai berbagai kekuatan gaib yang bersumber pada animisme dan dinamisme merupakan perbuatan musyrik dan merusak akidah, sehingga tidak bisa ditoleransi sama sekali. Kedua, sikap yang menerima tanpa reserve, ini dari kalangan awam yang tidak begitu paham Islam, tetapi mereka mendapatkan kemanfaatan dari tradisi tersebut, ini yang banyak diikuti masyarakat. Ketiga, sikap yang menghilangkan tradisi Jawa tetapi dengan cara persuasif dan bertahap. Islam disyiarkan melalui idiom lokal.